Ethics and personality essays in moral psychology (Univ. of Chicago Press, 1992)
Attachment, trust, respect, integrity, conscience, guilt, shame, revenge, depravity, gratitude, and forgiveness are among the topics discussed in this broad-ranging volume. This collection of thirteen essays focuses on emotions and motives that relate to our status as moral agents, our capacity for moral judgment, and the practices that help to define our social lives. Some of the authors develop new lines of thought within a recognized school of philosophy or a well-established program of research. Others present novel conceptions of their subject independently of any single school or program. Collectively, each essay in Ethics and Personality represents a time-honored tradition in ethics: studies designed to throw light on fundamental questions within the discipline through investigation of the complexities of the human soul. Ethics and Personality is a suitable text for advanced level courses and graduate seminars in ethics and philosophical psychology.